Phonics intervention DS - Nakeva von Mentzer, Cecilia (Uppsala University, 2018)
This SPSS dataset consists of test scores from 17 children with Down Syndrome who participated in a computer-based phonics intervention with a cross-over design over 8 weeks (one phase). Half participated one phase and half participated two phases. Children were tested with a naming test (phonological output), nonword repetition (phonological awareness) and decoding at 3 test points separated in time by four weeks (one phase). Some children started with phonics intervention while others attended regular school. Then groups were shifted. We also provide a pdf of the design of the study (mainly in Swedish).

The dataset was originally published in DiVA and moved to SND in 2024.

Detta SPSS-dataset består av testresultat från 17 barn med Downs syndrom som deltog i en datorbaserad fonetisk interventionsstudie med en cross-over-design under 8 veckor (en fas). Hälften deltog i en fas och hälften deltog i två faser. Barnen testades med ett namngivningstest (fonologisk output), upprepning utan ord (fonologisk medvetenhet) och avkodning vid tre testtillfällen som var åtskilda i tid med fyra veckor (en fas). Vissa barn började med den fonetisk interventionen medan andra gick i vanlig skola. Därefter skiftades grupperna. En pdf av studiens design finns också tillgänglig (huvudsakligen på svenska).

Translated with DeepL.com (free version)
Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Phonics intervention DS
Keywords: medicine (science); medicin; intervention study; interventionsforskning; Down syndrome; Downs syndrom; health sciences; hälsovetenskaper; phonetics; fonetik; Medical and Health Sciences; Medicin och hälsovetenskap